A memorial of Andrew J. Shipman: his life and writings - Shipman, Andrew Jackson (Encyclopedia Press, 1916)
--List of subscribers.--Resolutions.--Biographical sketch.--Spain of today.--Recent impressions of Spain.--An American Catholic's view of the Ferrer case.--McClure's Archer and Perrer.--The latest tactics as to Spain.--The situation in Portugal.--Immigration to the United States.--The Poles in the United States.--Our Italian Greek Catholics.--Catholics of the Eastern rites in the United States.--Moscow.--Glasgolitic.--Iconostasis.--Hungarian Catholics in America.--Slavs in America.--Slavonic language and liturgy.--Greek Catholics in America.--Rites in the United States.--Raskolniks.--Civic integrity.--A vision of American citizenship.--Stretching the Constitution.--The Catholic part in civic progress.--Roman Catholicism.--The church and art.--Cardinal Raphael Merry del Val.--Education and religion.--Manners maketh man.--Women in science.--Address to graduates of the College of New Rochelle, 1911.--Address to the graduates of Georgetown University, 1911.--The proposed Catholic association.